The speeches about children’s education and hygienization on the newspapers printed in Piauí, Brazil (1930-1960) - Oliveira, Vilma da Silva Mesquita (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> <![endif]-->DOI: http://dx.doi.org/10.14244/198271991473 <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> During the first half of the twentieth century Piauí, Brazil, was expanding its modernization process. In order to display a picture of full development, it was necessary to educate and take care of children, who were considered the nation's future, because, due to neglect, there was a growth in rates of child mortality. The goal of this study focuses on highlighting the measures adopted by the state to educate and care for children. Considering this context, this study highlights the childhood in Piauí, with the 1930’s beingthe starting point, which is a period in which there great evidence to infancy, and the ending being in 1960, when there were discussions focused on the child-problem, discourses circulated in printed newspapers at that time in Piauí (O Piauhy, Diário Oficial e O Dia). To perform this study, while considering the historical nature of the work, the theoretical research is based on the New Cultural History, which privileges the life history of common people, their daily lives, and their mindsets. The results indicate that social policies were created to improve this framework. The awareness of mothers in the care of their children was held in campaigns promoted by the state, such as robustness contests, courses in childcare, hygiene and nutrition for mothers, as well as advertisements of products that included guidance of this kind of care, in order to improve the vision of development in Piauí. Keywords: Education, Childhood, Newspapers, Piauí. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0cm; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE